Minority Influence and Degrowth-Oriented Pro-environmental Conflict: When Emotions Betray Our Attachment to the Social Dominant Paradigm - Avery, Robert A. T.; Butera, Fabrizio (Frontiers in Psychology, 2022)
If today the anthropogenic origin of climate change gathers almost total scientific consensus, human pro-environmental action is not changing with sufficient impact to keep global warming within the 1.5° limit. Environmental psychology has traditionally focused on the underlying barriers towards more pro-environmental behaviours. Emotions—like fear or anger—may act as such barriers especially in case of radical change (e.g., degrowth). While minority influence has been extensively applied to understand societal change, it has rarely been applied to understand the emotional responses that may hinder counter-normative pro-environmental messages. However, past literature on emotions shows that, in challenging situations —the likes of radical minority conflict—people will tend to use their emotional reaction to maintain societal status quo. Two studies investigated how participants emotionally react toward a counter-normative pro-environmental minority message (advocating degrowth). A qualitative (thematic analyses) and a quantitative (emotional self-report paradigm) studies showed that participants report emotions that allow them to realign themselves with the cultural backdrop of the social dominant paradigm (growth), thus resisting change. Specifically, although participants tend to demonstrate higher proportions of control-oriented emotions, men do so more. These effects, as well as questions of cultural and ideological dominance, are discussed considering barriers towards pro-environmentalism.